Burning bright [compact disc, unabridged] - Chevalier, Tracy (Penguin Audio, 2007)
"Burning bright" is a novel about the 18th-century English poet/painter William Blake and the children who sparked his "Songs of innocence" and "Songs of experience." In March of 1792, young Jem Kellaway and his family move from their small rural village in the Piddle Valley to the bustling city of London. Jem's father, a chairmaker, has agreed to hire on as a carpenter with Astley's Circus.